Analysis of the prognostic factors determining the oncological outcomes in patients with high-risk early-stage cervical cancer. (17th February 2022) - Kilic, Fatih; Cakir, Caner; Yuksel, Dilek; Korkmaz, Vakkas; Kimyon Comert, Gunsu; Boran, Nurettin; Koc, Sevgi; Turan, Taner; Turkmen, Osman
Abstract: We aimed to evaluate clinicopathological data in high-risk early-stage cervical cancer and to define the prognostic factors determining the oncological outcomes. This retrospective study included 158 patients with stage IB–IIA cervical cancer who underwent radical hysterectomy plus lymph node dissection. Each patient had at least one high-risk factor. The median tumour diameter of the study group was 30 mm (range, 6–80). Seventy-five (47.5%) patients had parametrial invasion, 32 (20.3%) had positive surgical margins, and 108 (68.4%) had lymph node metastasis. The median duration of follow-up was 42 months (range, 1–228). During this period, 28 patients developed recurrence, and the recurrent disease occurred in a distant area in 18 patients. Five-year disease-free survival was 77.5%, and five-year disease-specific survival was 85%. In multivariate analysis, adjuvant radiotherapy was identified as an independent prognostic factor for recurrence and death. The recurrence (Odds ratio: 10.139, 95% CI: 1.477–69.590, p = .018) and mortality rates (Odds ratio: 16.485, 95% CI: 2.484–109.408, p =.004) were higher in patients who did not receive adjuvant therapy. IMPACT STATEMENT: What is already known on this subject? The decision to proceed with adjuvant therapy in the patients with early-stage disease treated with surgery depends on the presence of risk factors in pathological examination. Various prognostic factors have been identified in cervical cancer (CC). However, there is a limited number of studies describing the prognostic factors in early-stage CC with high-risk factors. What do the results of this study add? In current study, the recurrence and mortality rates were higher in patients who did not receive adjuvant therapy. No relationship was found between the survival outcomes and the number of high-risk factors. Most of the patients who developed recurrence had the recurrence in the distant localisation. This result questioned the adequacy of adjuvant therapy. What are the implications of these findings for clinical practice and/or further research? There is still a debate over the prognostic factors and the adjuvant treatment options in the patients with early-stage cervical cancer who possess high-risk factors. Adjuvant RT or adjuvant concomitant chemoradiotherapy must definitely be used in this patients. However, adjuvant therapy fails approximately 14–32%, thus multimodal treatment modalities must be developed to improve the recurrence rates and the survival.